2021
DOI: 10.1177/1420326x211040242
|View full text |Cite
|
Sign up to set email alerts
|

Life-cycle cost analysis for façade retrofit measures of residential buildings in Cairo

Abstract: Nowadays, energy retrofit for existing buildings has become a worldwide approach to reduce total energy consumption. A wide range of energy-efficient retrofit measures is actively affecting the decision process, of which retrofit alternatives should be used. The existing study aims to evaluate the effects of façade retrofit measures in residential buildings in Cairo using life-cycle cost analysis. An extensive variety of façade retrofit alternatives was explored individually and combined. A hypothetical benchm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Secondly, increasing the WWR_S and decreasing the WWR_N and WWR_E of a building is critical to improving building performance. Literatures [37,98] are more consistent at the level of performance sensitivity analysis compared to the results derived from the optimization in this paper. It can be seen that window performance and the WWR of a building have a very significant effect on building performance, so more attention should be paid to this aspect in future research.…”
Section: At the Level Of Sensitivity Analysissupporting
confidence: 63%
See 2 more Smart Citations
“…Secondly, increasing the WWR_S and decreasing the WWR_N and WWR_E of a building is critical to improving building performance. Literatures [37,98] are more consistent at the level of performance sensitivity analysis compared to the results derived from the optimization in this paper. It can be seen that window performance and the WWR of a building have a very significant effect on building performance, so more attention should be paid to this aspect in future research.…”
Section: At the Level Of Sensitivity Analysissupporting
confidence: 63%
“…Kazem et al went on to explore the effectiveness of energy efficiency retrofits in Cairo buildings through a whole-life-cycle cost analysis. The results showed that the most cost-effective façade retrofit was the installation of 1 m long external shading facilities, which reduced LCC by 1.4% and energy consumption by 18% [37]. Weerasinghe et al went on to analyze the impact of green building costs in Sri Lanka by examining the life cycle costs of the building in its aspect.…”
Section: At the Level Of Building Life Cycle Costsmentioning
confidence: 99%
See 1 more Smart Citation